THE HOLY QUR’ÓN’S VOICE OF REVOLUTION AGAINST LANDLORDS - AMNA IMAM (Hamdard Islamicus, 2021)
One of the major causes of economic exploitation in any society is the unnatural and invalid land tenure system. In other words one of the main reasons for economic exploitation and class system is the unlimited land ownership. Under this class system there are two types of classes in the society. The first group comprises persons who have established a monopoly on land ownership and production based on their economic power and influence. We call them “Feudal Lords” or “Landlords”. They have nothing to do with hard work but their share of land production for them is allocated in all cases. The second group consists of those persons who work hard day and night to irrigate lush gardens and fields with their blood and sweat. Despite turning the earth’s soil into gold, the benefit of their success is merely two loaves of bread to fill the stomach and modest clothing to cover their body. Due to the tyranny and economic domination of these landlords, the poor farmers are economically exploited. In Pakistan, economic exploitation of poor and helpless farmers by landlords on the basis of economic and political power continues from generation to generation. This article identifies various forms of economic exploitation by landlords. At the same time, in the light of teachings of The Holy Qur’Én and Sunnah, the correct form of the landlord system has been presented. In addition, an alternative way has also been offered by ‘Umar (RaÌi Allah ‘anhu) against the false system of feudalism which exists in Islamic history in the form of an IjtihÉd about KharÉj. The author believes that the promise of Islam regarding economic and social prosperity of the Muslim Ummah may be fulfiled only if this alternative path is adopted.